Proposition - Impressions about guitar and vocality in a song by Ricardo Tacuchian - Mattos, Wladimir F. C. [UNESP]; Lourenco Jr, Lourival [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2020)
More than a neologism proposed to give effect to some conceptual game, the term guitarism, in contrast to guitaristc, reflects a conception about the specific behavior of the guitar in the practice of the Brazilian art song. It is about the possibilities of the guitarist's performance in the art song for voice and guitar, especially when we realize that this repertoire has at the heart of its creation not only the setting of a poem to music in the composition of a singable melody, to be accompanied by, but a process in which this music and its intrinsic vocality integrate the instrument in the three-dimensional discursive unit of this type of song. As an exercise in analyzing these possibilities, we present some impressions about Proposicao, a song by Ricardo Tacuchian, with text by Gabriel Neves.
Keywords: Classical guitar; Guitarism; Vocality; Art song